Introductory genetics for statisticians - Elston, Robert (Henry Stewart Talks, 2004)
Physical basis of the human genotype, Meiosis, Genotype vs. phenotype, Genetic distance, Mendelian segregation, Dominance and recessiveness, Hardy-Weinberg proportions, Heritability (broad sense and narrow sense), Additive polygenic models, Applications to binary and continuous traits, Identity-by-descent, Covariance between relatives, Locus-specific genetic variance, Concepts of linkage analysis, Concepts of association analysis
Archived at 2021/02/25